Novel Diagnostic and Therapeutic Approaches in Temporomandibular Disorders (TMDs) and Myofascial Pain - Nowak, Zuzanna; Nitecka-Buchta, Aleksandra (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aimed to cover a diverse scope of topics, from diagnostics to the management of temporomandibular disorders and myofascial pain, with a special focus on innovations in those areas. Intense research progress in the subject as well as technological development, access to knowledge, and novel digital tools allow developing more precise, reproducible, and dedicated diagnostic and therapeutic protocols.